Detection of long nulls in PSR B1706−16, a pulsar with large timing irregularities. Issue 2 (21st December 2017) - Naidu, Arun; Joshi, Bhal Chandra; Manoharan, P K; Krishnakumar, M A
Abstract: Single pulse observations, characterizing in detail, the nulling behaviour of PSR B1706−16 are being reported for the first time in this paper. Our regular long duration monitoring of this pulsar reveals long nulls of 2–5 h with an overall nulling fraction of 31 ± 2 per cent. The pulsar shows two distinct phases of emission. It is usually in an active phase, characterized by pulsations interspersed with shorter nulls, with a nulling fraction of about 15  per cent, but it also rarely switches to an inactive phase, consisting of long nulls. The nulls in this pulsar are concurrent between 326.5 and 610 MHz. Profile mode changes accompanied by changes in fluctuation properties are seen in this pulsar, which switches from mode A before a null to mode B after the null. The distribution of null durations in this pulsar is bimodal. With its occasional long nulls, PSR B1706−16 joins the small group of intermediate nullers, which lie between the classical nullers and the intermittent pulsars. Similar to other intermediate nullers, PSR B1706−16 shows high timing noise, which could be due to its rare long nulls if one assumes that the slowdown rate during such nulls is different from that during the bursts.